Decir la verdad, hacer justicia: Los Juicios por la Verdad en Argentina - Andriotti Romanin, Enrique Salvador (2013)
Tell the Truth, Do Justice: The Truth-Finding Trials in Argentina In the late 90’s the so-called “Truth-Finding Trials” made their appearance in different cities of Argentina. In the course of the hearings, the families and survivors spoke out against the magnitude of repression and the civil participation in state terrorism; individual members of the Armed Forces were forced to attend law courts to testify. For these reasons, from the beginning, these “trials” generated strong conflicts and political disputes mainly between the State, the human rights movement and other social actors interested in either promoting or blocking a judicial review of the dictatorial past. In the present work we investigate some dimensions little explored in the bibliography specialized on the truth-finding trials, particularly in the strategies used to achieve the same. The idea guiding this article is that these trials were the result of different legal, political and procedural strategies, which taken together allow the visualization of different methods used in the construction of these trials